I feel pretty [videorecording (DVD)] - Kohn, Abby; Schumer, Amy; Williams, Michelle, 1980-; Scovel, Rory (Universal Pictures Home Entertainment, 2018)
A woman struggling with insecurity wakes from a fall believing she is the most beautiful and capable woman on the planet. Her new confidence empowers her to live fearlessly, but what happens when she realizes her appearance never changed?